Application of Kahoot Media in Indonesian Language Learning for Grade V Students of Elementary School Aisyiyah Unggulan Gemolong - Septia Ardiana; Sukartono Sukartono (Universitas Negeri Semarang, 2024)
In the digital era, technology integration in learning is one of the solutions to increase student motivation and participation. One innovation that has been implemented is the use of digital-based interactive media, such as Kahoot, which is designed to make the learning process more interesting. This study aims to: 1) describe the planning of Kahoot media application in Indonesian language learning, 2) describe the application of Kahoot media in Indonesian language learning, 3) describe the supporting factors and inhibiting factors of Kahoot media application in Indonesian language learning, and 4) describe solutions to overcome the inhibiting factors of Kahoot media in Indonesian language learning. The research method used is descriptive qualitative. This research design is a case study involving research subjects in the form of 1 teacher and fifth grade students of Aisyiyah Unggulan Gemolong Elementary School. Data collection techniques used observation, interviews, and documentation. Efforts to test the validity of data using triangulation of sources and techniques. The data obtained were then analyzed through data reduction, data presentation, and conclusion drawing. This research can contribute to the development of more engaging and interactive teaching methods, as well as support teachers in designing more effective teaching strategies. Additionally, the findings of this research can provide guidance for other schools to integrate technology into the learning process, thereby enhancing the overall quality of education.